c.1 - Subramanian, S. (ed.) (New Delhi, 1997)
This is a collection of writings on the measurement of poverty and inequality, a phenomenon widely observed in all modern societies. The book presents concepts and techniques, and their application in a developing country context, focusing on measurement-related issues.
Keywords: Poverty